Congenital tracheobiliary fistula: Diagnostic and surgical management - Salman M. Ghazwani; Sani Rabiou; Yahya D. Otaif; Mohammed O. Shami; Majed A. Alibrahim; Fahd M. Somili (Elsevier, 2023)
Introduction: Congenital tracheobiliary fistula is an uncommon condition that affects both infants and adults. The early onset of symptoms is associated with severe diseases. Diagnosis of the disease in infants is difficult since children seldom exhibit the characteristic bile-colored sputum. Case presentation: The authors report the case of congenital tracheobiliary fistula in the neonatal context. The diagnosis was reached as a result of respiratory distress with yellowish drooling coming from the endotracheal tube. A computerized tomography scan confirmed the diagnosis. Surgery by thoracotomy allows for the dissection and division of the fistula. Conclusion: The surgical approach is the preferred treatment method, with a thoracotomy procedure and fistula repair. Due to potential complications during the surgical operation and the postoperative period, a follow-up is required to monitor the symptoms and ensure overall recovery.